2013
DOI: 10.1038/nrgastro.2013.35
|View full text |Cite
|
Sign up to set email alerts
|

The gastrointestinal mucus system in health and disease

Abstract: Mucins—large, highly glycosylated proteins—are important for the luminal protection of the gastrointestinal tract. Enterocytes have their apical surface covered by transmembrane mucins and goblet cells produce the secreted gel-forming mucins that form mucus. The small intestine has a single unattached mucus layer. In cystic fibrosis, this layer becomes attached, accounting for the intestinal manifestations of this disease. The stomach and colon have two layers of mucus; the inner layer is attached and the oute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
1,023
0
22

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,127 publications
(1,059 citation statements)
references
References 154 publications
14
1,023
0
22
Order By: Relevance
“…They are also universally distributed on neurons, thus allowing them to respond to bacterial and viral components (Reis et al, 2015). While the intestinal epithelium and the mucus layer acts largely as a barrier to translocation of microorganisms into the internal milieu, the nervous system is prepared and capable of responding to such interactions (Johansson et al, 2013). The initial microbial colonization results in significant changes in mucosal and systemic immunity.…”
Section: Microbes and Immunitymentioning
confidence: 99%
“…They are also universally distributed on neurons, thus allowing them to respond to bacterial and viral components (Reis et al, 2015). While the intestinal epithelium and the mucus layer acts largely as a barrier to translocation of microorganisms into the internal milieu, the nervous system is prepared and capable of responding to such interactions (Johansson et al, 2013). The initial microbial colonization results in significant changes in mucosal and systemic immunity.…”
Section: Microbes and Immunitymentioning
confidence: 99%
“…Dans l'iléon terminal, où la densité en bactéries augmente fortement, les cellules de Paneth présentes dans les cryptes contribuent, avec les entérocytes adjacents, à la production de peptides microbicides qui coopèrent avec le mucus sécrété par les cellules spécialisées, pour réduire les contacts entre bactéries et épithélium [3]. Dans le côlon, où la densité des bactéries est maximale, le nombre de cellules à mucus augmente considérablement, permettant la formation d'un film muqueux épais, en deux couches : une couche externe fluide, où s'accumulent les bactéries qui y puisent les substrats nécessaires à leur croissance, et une couche interne très dense et quasiment stérile, limitant les contacts directs des bactéries avec la surface épithéliale [4]. Le déclenchement spontané d'une inflammation intestinale chez des souris dont la production de mucus est compromise, souligne 1 Environ 97 % de la masse vivante sur notre planète sont représentés par des microorganismes qui colonisent tous les environnements accessibles sur terre.…”
Section: L'épithélium Intestinal Premier Rempart Contre Les Bactérieunclassified
“…l'importance de ce mécanisme dans la préservation de l'homéostasie intestinale face au microbiote. Chez l'homme, des altérations des cellules de Paneth et des cellules à mucus sont respectivement mises en cause dans la pathogénie de la maladie de Crohn et de la rectocolite hémorragique [3,4]. L'étude de souris gnotoxéniques (des souris élevées dans des conditions stériles puis colonisées par des bactéries individuelles ou des microbiotes complexes [5]) montre que la colonisation intestinale modifie la nature et la quantité du mucus, et induit la production de peptides microbicides [3].…”
Section: Les Cellules Lymphoïdes Innéesunclassified
See 1 more Smart Citation
“…The mucus layer consists of a mixture of water, complex glycosylated molecules (mucins), and antimicrobial proteins [7]. Studies of the mucus layer in HSCR have shown changes in both mucins and secreted immunoglobulin in patients with HAEC [8], [9], [10].…”
Section: Introductionmentioning
confidence: 99%